Β‐Cyclodextrin Complex Containing Lippia grata Leaf Essential Oil Reduces Orofacial Nociception in Mice – Evidence of Possible Involvement of Descending Inhibitory Pain Modulation Pathway. (8th November 2013) - Siqueira‐Lima, Pollyana S.; Araújo, Adriano A. S.; Lucchese, Angélica M.; Quintans, Jullyana S. S.; Menezes, Paula P.; Alves, Péricles B.; de, Waldecy; Santos, Marcio R. V.; Bonjardim, Leonardo R.; Quintans‐Júnior, Lucindo J.
Abstract The treatment of orofacial pain remains a major challenge for modern medicine. Thus, we prepared and physicochemically characterized a new β‐cyclodextrin complex containing Lippia grata leaf essential oil (β‐CD/EO) to investigate their possible antinociceptive activity in animal models of orofacial pain. The results of Differential scanning calorimeter (DSC) and Thermogravimetry/derivative thermogravimetry (TG/DTG) showed that the products prepared by Slurry complexation (SC) method were able to incorporate greater amounts of EO. In the X‐ray diffractogram, it was shown that complex between EO and β‐CD was formed. Male Swiss mice were pre‐treated with β‐CD/EO (6, 12 or 24 mg/kg, per os, gavage, p.o.), morphine (5 mg/kg, i.p.) or vehicle (distilled water, p.o.) 1 hr before treatment with formalin (20 μL, 2%), capsaicin (20 μL, 2.5 μg) or glutamate (40 μL, 25 μM) into the right upper lip. Our results demonstrated that p.o. treatment with β‐CD/EO was significantly (p < 0.05 or p < 0.001) capable of reducing the nociceptive face‐rubbing behaviour in both phases of the formalin test. β‐CD/EO‐treated mice were also significantly (p < 0.05 or p < 0.001) protected against nociception induced by capsaicin and glutamate. For the action in the central nervous system (CNS), ninety minutes after the treatment, the mice were perfused, the brains collected, crioprotected, cut in a criostate and submitted to an immunofluorescence protocol for Fos protein. The immunofluorescence protocol demonstrated that the β‐CD/EO significantly activated (p < 0.05; p < 0.01 or p < 0.001) the motor cortex, the Locus ceruleus, the nucleus raphe magnus and the periaqueductal gray of the CNS. These effects apparently did not alter, in tested doses, the motor coordination of mice in the rota‐rod test. Our results proposed that β‐CD/EO might present an important draft of drug to the study of new compounds for the treatment of orofacial pain.